ERS International Congress 2023: highlights from the Airway Diseases Assembly - Bergantini, Laura; Baker, James; Bossios, Apostolos; Braunstahl, Gert-Jan; Conemans, Lennart H.; Lombardi, Francesco; Mathioudakis, Alexander G.; Pobeha, Pavol; Ricciardolo, Fabio Luigi Massimo; Romero, Leidy Paola Prada; Schleich, Florence; Snelgrove, Robert J.; et al. (ERJ Open Research, 2024)
In this review, early career and senior members of Assembly 5 (Airway Diseases, Asthma, COPD and Chronic Cough) present key recent findings pertinent to airway diseases that were presented during the European Respiratory Society International Congress 2023 in Milan, Italy, with a particular focus on asthma, COPD, chronic cough and bronchiectasis. During the congress, an increased number of symposia, workshops and abstract presentations were organised. In total, 739 abstracts were submitted for Assembly 5 and the majority of these were presented by early career members. These data highlight the increased interest in this group of respiratory diseases.